The verse of the translations into Czech of Life is a Dream: the case of octava - Darebny, Jan (Romanica Olomucensia, 2015)
The objective of this article is to present the methodology used in the author's investigation which deals with a comparison of Spanish dramatic verse and its translations into Czech from the point of view of versology and the theory and history of translation. In this study the verse of the four Czech translations of Calderon de la Barca's play Life Is a Dream is analysed.
Keywords: verse; play; Calderon de la Barca; Life Is a Dream; translation.